The factors that affect unemployment among graduates in Johor Bahru / Mohd Fahmi Hamdan and Izwan Nazirin Ismail - Hamdan, Mohd Fahmi; Ismail, Izwan Nazirin (Faculty of Business and Management, 2013)
This project paper entitled “The Affecting of Unemployment among Graduates Student” was conducted from February 2012 until July 2012. The researchers came out with this project paper to find the most contribute factors toward unemployment among graduates student around Johor Bahru. This study focuses on four important independent variables which are poor communication skill, lack of experience, too picky on job and mismatch of major course with the job opportunities. The research was done at JobsMalaysia Centre Iskandar Malaysia, where the data and statics are being taken. Through this research, researchers are able to know the factors that affect unemployment among graduates student. Researchers also have better understanding on the reason towards the increasing rate of the unemployment graduates nowadays and be able to share knowledge with public. Basically, through such research, researchers now has gain a better understanding of concepts, techniques and skills acquired during the program, through application in real situations. Besides that, researchers have also improved the ability to write a substantial report in a well-structured manner. In addition, with this research, it is hope that the student are more aware to the factor that affect unemployment among them and be more flexible toward the job that has been offer to them after they graduated.